Desempenho de Um Wetland Com Fluxo Vertical (Modelo Francês) no Tratamento de Esgoto Sanitário - Pombal, Vitor Luiz Viana (2022)
The objective of this project was to evaluate the performance of a pilot wetland treatment plant for domestical wastewater using the first stage with two modules of a French model, applying different operational conditions. Each reservoir has 1,80x1,80x1,20 m dimentions, filled with gravel 0,1 and 3 and vegetated with Typha domingensis. A lift tank with two parallel pumping system to make batch loads assured the pilot feeding with raw wastewater, applied hydraulic loads of 0,3, 0,4, 0,6 and 0,8 m³/m².d to make the performancy tests. It was necessary to make adaptations such as shadow screen installation and hydraulic feeding reduction to reduce organic stressing, making that the system made the permanent regime in about 55 days. After 180 days of operation, it was made the first pruning of the plants that grew up over 2 m. The development of the biofilm and rhizosphere have an important matter in wastewater treatment, it is where part of organic matter and suspended solids are retained. The sludge is partialy constituted of elements that make contribution in phosphorus removal, such as calcium and iron, which induced a global efficiency of 28% of P removal, superior of national average indicated for the first stage of this kind of wetland filter. During applications of 0,3 m³/m².d, the P removal efficiency were 24%, equally for 0,4 m³/m².d when it was observed the formation of the sludge deposit in a module. Flow ratings of 0,6 m³/m².d the average efficiency of total phosphorus removal were 32% when sludge deposit was established in both reservoir, and at 0,8 m³/m².d ratings the average was 31%. The phosphorus removal efficiency was proportional to the growth of sludge layer, which developed in a 1,12 cm/year rating, similar to national averages. For the other evaluated parameters, the system contributed with removals of 53% NTK, 59% of N-NH4 + , 21% of P-PO4 3- , 47% of TSS, 70% of BOD, 53% of COD, 47% of turbidity and 11% of coliforms removal, those agreed with CONAMA patterns for sewage discharge. The average treated effluent characteristics were: 17 mg NTK/L; 6,64 mg N-NH4 + /L; 11,95 mg Ptotal/L; 9,46 mg P-PO4 3- /L; 134,5 mg SST/L; 95,5 NTU of Turbidity; pH of 7,5; 1,46 mg OD/L; 194,5 mg DQO/L; 99,5 mg DBO /L. These results were in accordance with averages required by CONAMA 430 resolution of 2011.